The lavidge and steiner hierarchy of effects model for advertising: a framework of Islamic advertising - Mokhtar, Aida (2015)
Advertising effectiveness could be measured by the hierarchy of effects model by Lavidge and Steiner (1961). It depicts the various steps prospective consumers go through before making a purchase. Advertising is the force that is able to move consumers along the different steps. The purpose of life for a Muslim is to worship Allah. In view of this, all Muslims should receive guidance from the Qur’an and Sunnah. Advertising effectiveness has to be examined in accordance with these sources. A framework amalgamating a hierarchy of effects model and Islamic principles is created to assist advertisers in their decision making.